ChemInform Abstract: Direct Synthesis of Protoberberine Alkaloids by Rh‐Catalyzed C—H Bond Activation as the Key Step. Issue 24 (27th May 2016) - Jayakumar, Jayachandran; Cheng, Chien‐Hong
Abstract: A one‐pot reaction of substituted benzaldehydes with alkyne—amines by Rh‐catalyzed C—H activation and annulation to afford various natural and unnatural protoberberine alkaloids is reported.